Challenges in Implementation of Integrated Curriculum-Insights from Faculty’s Perspectives - Kainat Javed; Muddasar Ali; Noor-i-Kiran Naeem (Journal of Aziz Fatimah Medical and Dental College)
Objective: The purpose of this study was to explore the barriers regarding implementing integrated undergraduate curriculum perceived by medical faculty. Methodology: From October - November 2023, a qualitative exploratory study was carried out at undergraduate medical college that successfully implemented integrated curriculum. We recorded and transcribed a total of twelve semi-structured interviews. Faculty perspectives of the issues preventing a smooth transition to an integrated curriculum were investigated both before and after it was implemented, using a thematic content analysis approach. Results: Faculty who had seen the programme firsthand determined that four initial barriers were genuine: faculty reluctance, a lack of rewards, inadequate resources, and a lack of preparation. Following the event, four more barriers were found, including a lack of administration, a disregard for the concerns of the faculty, a communication breakdown, and challenges in determining suitable assessment. Conclusions: Curriculum integration at undergraduate medical institutions may fail for a number of reasons if they are overlooked. The regulatory agency should establish relevant and adequate policies to guarantee the control over the obstacles.